Book Review: Teologi Crucis di Asia Pandangan-Pandangan Orang Kristen Asia Mengenai Penderitaan Dalam Kemiskinan dan Keberagamaan di Asia: Book Review: Crucis Theology in Asia The Views of Asian Christians Regarding the Suffering of Poverty and Religion in Asia - Arthur Aritonang (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
This book is Andreas A. Yewangoe's doctoral dissertation while studying at Vrije Universiteit in Amsterdam, The Netherlands. Its contents present a portrait of poverty in Asia, which was experiencing colonization by Western nations and Japan. In this book, Yewangoe focuses on the problem of poverty, specifically in Indonesia. The West knows the Asian continent as a religious continent because it contains a diversity of religions. However, most of the population is in the poverty line. This fact prompted Yewangoe to ask several critical questions, which were the subject of analysis in his dissertation. Why is it that a religious country has a substantial population of poor people? Does religion legitimize suffering due to poverty suffering? For what purpose is suffering due to poverty? Yewangoe, in his book, uses several analytical perspectives, including: historical, social, political, economic, and cultural. Thus, through this book, he will answer these questions completely.